The most factor that influence the road accidents by using fuzzy logic method / Nuramira Omar Yahya - Omar Yahya, Nuramira (2021)
Accidents are nightmares for anyone who has experienced that before, no matter how bad the injury was and there is no one in this world willing to be involved in any accidents. However, changes of attitudes towards road users are an often advocated condition for improving road safety. Although various safety campaigns have been carried out in Malaysia, the attitude of reckless road users can still lead to accidents to be happened. There are factors that cause accidents and this study investigated the factor that influences the most in fatal road accidents. The factors chosen in this study are environmental error, human error, and health factor, which are gained from literature review. To perform this study well, the data were collected through an online survey, which consists of 298 respondents who have and have not experienced an accident before. An expert system has been developed by using a fuzzy logic approach to determine which one of the chosen factors is most influencing in road accidents. The results perform in the MATLAB software shows that health factor is the most influential in road accidents. Findings from this study would assist the people all around the world to stay healthy and to take care of themselves since accidents can happen anywhere.